Synthesis and Characterization of Nanostructured Copper Oxide Thin Films Prepared by Home-Made DC Magnetron Sputtering for Gas Sensor Applications - Dawood, Basima Saleem (Indonesian Journal on Health Science and Medicine, 2025)
In this research, high-quality nanostructured copper oxide (CuO and Cu2O) thin films were prepared by home-made dc magnetron sputtering technique. The properties and characterizations of the prepared nanostructure films have been determined by the ratios of gases (argon and oxygen) inside the discharge chamber, and heat treatment (annealing) of these films around 400 Co. These parameters were effectively realized important to control the structural characteristics of the prepared nanostructures, especially the energy band gap Eg which was determined by using uv-visible measurements, and particles size. The phase structures of cupric and cuprous were examined by X-ray diffraction to compare between two phases. The type of copper oxide semiconductors two distinct phases: cuprous oxide (Cu2O), and tenorite (CuO) was determined through Hall effect measurement which was indicated in P-type binary copper oxide. The phases of copper oxide nanostructures were successfully verified for gas sensing applications and they exhibited reasonably high sensitivity with increasing temperature (up to 96% at 350°C). This work can be good attempt to use copper oxide nanostructures in such important application. Highlights: Nanostructured CuO and Cu₂O thin films were successfully fabricated using a home-made DC magnetron sputtering technique under varying Ar:O₂ gas ratios. XRD and FTIR analyses confirmed the formation of distinct CuO and Cu₂O phases with controlled crystallinity and optical band gaps of 2.33 eV and 2.9 eV, respectively. The prepared films exhibited high gas sensitivity, reaching 96% at 350 °C, particularly toward NO₂, demonstrating strong potential for gas sensor applications.